Urtikaria - Daut, V.; Hörmann, Karl; Klimek, Ludger; Pfaar, Oliver (HNO, 2012)
Urticaria describes a heterogeneous group of diseases, whose cardinal symptoms are itching wheals. With a high life time prevalence of 25%, this disease is of major relevance, and the ENT specialist should be familiar with this disease. The most common type is spontaneous Urticaria in which the wheals seem to arise without provocation. Its subtypes are acute and chronic. The mechanism of wheal formation is the activation and degranulation of mast cells. However, the etiology of the wheals is multifaceted. In case of acute spontaneous urticaria, the underlying cause does not have to be verified. It is treated symptomatically by its self-limiting course of disease. The chronic spontaneous, less frequent form of urticaria is treated curatively by identification and elimination of underlying causes, such as autoimmune processes, intolerance to food additives and chronic infections. The chronic subtype can persist for years and thus has an extensive socioeconomic impact. This article overviews the clinical symptoms, diagnostic methods and therapeutic options for both acute spontaneous and chronic spontaneous urticaria, and refers to the current international EAACI/WAO and German DGAKI/DDG S3 guidelines.